PELESTARIAN ARSITEKTUR LANGGAR DHUWUR MBAH YAI MASTUR LAMONGAN - Hammam Rofiqi Agustapraja (Jurnal Teknika, 2018)
Langgar  Dhuwur  Mbah  Yai  Mastur  is  a  lifted  small  mosque  established  by  Hadratus  Syaikh  KH.  Mastur Asnawi, until now it is still used for the activities of the Tahfidhul  - Qur'an Islamic Boarding School, in terms of architecture, this  building  has different characteristics from the surrounding buildings, namely a simple design in the form of a stage made of wood and roofed with traditional roof (Limasan), so that the existence of  meaning Historically  this  violation  has  not  been  eroded  by  development,  so  the  need  for  research  on  architectural preservation  with  the  consideration  that  this  object  has  fulfilled  the  requirements  of  the  Cultural  Heritage Objects  Act  No.  11  of  2010,  the  method  used  to  examine  the  preservation  of  architecture  is  a  method  of qualitative  analysis  using  an  approach  with  three  methods,  namely  analysis  description  method,  evaluative method  and  development  method.  The  results  of  this  study  indicate  that  some  visual  elements  of  Langgar Dhuwur  are  still  permanent,  which  can  be  known  through  observation  on  the  object  of  study.  Preservation directives  for  building  visual  elements  are  classified  into  three  potential,  namely  low,  medium  and  high potential, then from the three potential levels, preservation actions will be determined